2007
DOI: 10.1088/1742-2132/4/3/s06
|View full text |Cite
|
Sign up to set email alerts
|

The effect of changing scatterer positions on acoustic time-reversal refocusing in a 2D urban environment at low frequencies

Abstract: In a previous work, we considered time-reversal refocusing for localizing a sound source in a highly reverberant urban environment with non-line-of-sight (NLOS) receivers. The approach involved a virtual (computer-based) time-reversal propagation calculation using a priori knowledge of the receiver and scatterer positions. Among the errors that affect the quality of refocusing is the imperfect accuracy of the assumed scatterer locations. Some practical analogues of changing scatterer positions are (a) the buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…While many studies have been done on the consequences of imperfect models 23 and it is almost always assured that model uncertainty will degrade beamformer performance, the extent of the degradation is both model specific and highly dependent on the array-source geometry as shown previously. To quantify the impact of mismatch on performance, it is necessary to search a large domain.…”
Section: B Spatial Variation Of Performancementioning
confidence: 93%
See 1 more Smart Citation
“…While many studies have been done on the consequences of imperfect models 23 and it is almost always assured that model uncertainty will degrade beamformer performance, the extent of the degradation is both model specific and highly dependent on the array-source geometry as shown previously. To quantify the impact of mismatch on performance, it is necessary to search a large domain.…”
Section: B Spatial Variation Of Performancementioning
confidence: 93%
“…Some of the effects of model uncertainty have been studied in the context of time reversal refocusing. Liu et al 23 found that localization was generally tolerant of minor changes in scatterer position, although the addition of an obstacle close to a receiver caused substantial degradations. Yon et al 15 reported similar robustness to perturbations such as moving persons within a room.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that time-reversal is a self-averaging process and can focus a signal back to its source in a multiple scattering environment and that source localization is successful when a broadband impulse is transmitted rather than a single frequency signal [1]. Time-reversal was also shown to be effective in locating a perturbation in a 2D urban environment [2]. This is important because an urban environment presents the challenge of large objects obscuring acoustic receivers and sources as there is no direct line-of-sight path from an acoustic source to any receivers.…”
Section: Theorymentioning
confidence: 99%
“…1. 12,14,15 This flat area has 15 closely spaced concrete buildings arranged in a 200 m by 140 m area. The impulsive sound source was placed at the center of the main street Locations of the buildings, the acoustic source (the asterisk, the location is referred as S1 hereinafter), and receivers for the numerical experiments.…”
Section: Building and Street Modelmentioning
confidence: 99%